Penguatan Perilaku âNgeloni Anakâ Oleh Ibu-Ayah sebagai Upaya Menciptakan Keluarga Harmonis-Seimbang Sejak Dini - Rahmatullah, Azzam Syukur (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2016)
One of important aspects in educating children to have a harmonious, balanced, and lasting family is to concern on parenting since early times. One of the ways is to hug a child. This paper discusses the importance of child development so they can build a harmonious family. When the parent demonstrates their affections to their children by hugging, the children will get a double touch from their parent (father and mother) and they do not get the touch from one of them. Hugging children has a big role to child development in the future. The more the parent gives a sincere affection, positive situation, friendship, the more children will get strong of personality. A good and health personality will affect self-children positively when they build a family to become a harmony family. On the contrary, the less the parent give a warm hugging likes no affections and sincerity, derision, insult and reproach; the more the children will get a sick personality. Such personality will be a problem for children either in the present times or during the development period from childhood to teenage and adult.Â Ø£ØØ¯ Ø§ÙØ¬ÙØ§ÙØ¨ Ø§ÙÙØ§ÙØ© Ø§ÙÙØ¤Ø¯ÙØ© Ø¥ÙÙ Ø£Ù ØªÙÙÙ Ø£Ø³Ø±Ø© Ø§ÙÙÙØ¯ ÙÙ Ø§ÙÙØ³ØªÙØ¨Ù Ø£Ø³Ø±Ø© Ø³Ø¹ÙØ¯Ø© ÙØ³ØªÙØ±ÙØ© ÙÙÙ Ø¯ÙØ§ÙÙÙØ§ ÙÙ ÙÙØ· Ø§ÙØØ¶Ø§ÙØ© Ø§ÙØµØÙØØ© ÙÙØ° Ø§ÙØ¨Ø¯Ø§ÙØ©. Â ÙÙÙ ÙÙÙÙØ§Øª Ø§ÙØØ¶Ø§ÙØ© ÙØ§ÙØªØ±Ø¨ÙØ© ÙÙ ØªØØ¶ÙÙ Ø§ÙÙÙØ¯ ÙÙØ¹Ø§ÙÙØªÙ. ØØ§ÙÙØª ÙØ°Ù Ø§ÙÙÙØ§ÙØ© ÙÙØ§Ø´ Ø£ÙÙÙØ© " ÙØ¹Ø§ÙÙØ© Ø§ÙØ£Ø¨ÙØ§Ø¡" Â ÙÙØ´ÙØ¦ÙÙ ÙØªØ·ÙÙØ±ÙÙ ØØªÙ ÙÙÙÙÙØ§ ÙÙ Ø§ÙÙØ³ØªÙØ¨Ù Ø£Ø³Ø±Ø© Ø³Ø¹ÙØ¯Ø© ÙØ³ØªÙØ±ÙØ©. Ø¨ÙØ°Ù Ø§ÙØ¹ÙÙÙØ© - ÙØ¹Ø§ÙÙØ© Ø§ÙØ£Ø¨ÙØ§Ø¡- Ø³ÙØØµÙ Ø§ÙØ£Ø¨ÙØ§Ø¡ Ø¹ÙÙ Ø§ÙÙÙØ³ØªÙÙ ( Ø§ÙÙØ¹Ø§ÙÙØ© Ø§ÙØØ§Ø±Ø© ÙÙ Ø§ÙÙØ§ÙØ¯ÙÙ) ÙØ§ ÙÙ Ø·Ø±Ù ÙØ§ØØ¯ ÙÙØ·( Ø§ÙØ£Ù). ÙÙØ¹Ø§ÙÙØ© Ø§ÙØ£Ø¨ÙØ§Ø¡ ÙÙØ§ Ø¯ÙØ± ÙØ¨ÙØ± ÙÙ ÙÙÙÙ Ø§ÙØ£Ø¨ÙØ§Ø¡ ÙØªØ·ÙÙØ±ÙÙ ÙÙ Ø§ÙÙØ³ØªÙØ¨Ù. Ø¥Ø°Ø§ ØªÙØ±ÙØ±Øª ÙØ°Ù Ø§ÙÙØ¹Ø§ÙÙØ§Øª â ÙÙÙÙØ§ Ø§ÙØ±ØÙØ© ÙØ§ÙØ´ÙÙØ© ÙØ§ÙØ¯ÙØ§ÙØ¹ Ø§ÙØ¥ÙØ¬Ø§Ø¨ÙØ©Ø ÙØ§ÙÙØªØ£ÙÙÙ ÙØ§ÙÙØµØ§ØØ¨Ø© â Ø£Ø¹Ø·Øª ÙÙØ£Ø¨ÙØ§Ø¡ ÙØ±ØµØ§ ÙÙÙÙÙÙØ§ Ø£Ø¨ÙØ§Ø¡Ø§ Ø°ÙÙ Ø´Ø®ØµÙØ§Øª ÙÙÙØ© Ø³ÙÙÙØ©. Â ÙÙØ°Ù Ø§ÙØ´Ø®ØµÙØ§Øª Ø§ÙÙÙÙØ© Ø§ÙØ³ÙÙÙØ© Ø³ØªØ¤Ø«ÙØ± Ø¥ÙØ¬Ø§Ø¨ÙØ§ Ø¹ÙÙ ÙÙÙØ³ Ø§ÙØ£Ø¨ÙØ§Ø¡ ØÙÙ ØªØ²ÙÙØ¬ÙØ§ ÙØ³ØªØµØ¨Ø Ø£Ø³Ø±ØªÙÙ Ø£Ø³Ø±Ø© Ø³Ø¹ÙØ¯Ø©. ÙØ§ÙØ¹ÙØ³ Ø¥Ø°Ø§ ÙÙÙØª ÙØ°Ù Ø§ÙÙØ¹Ø§ÙÙØ§Øª â ÙØ¨ÙØ§ ÙÙÙØª Ø§ÙØ±ØÙØ© ÙØ§ÙØ´ÙÙØ© Ø¨Ù ØµØ¯Ø± ÙÙ Ø§ÙÙØ§ÙØ¯ÙÙ Ø§ÙØ¹ØªØ§Ø¨ ÙØ§ÙØªØÙÙØ± ÙØºÙØ±ÙÙØ§ â ÙØ³ØªØ¤Ù Ø¥ÙÙ Ø£Ù ØªÙÙÙ Ø´Ø®ØµÙØ© Ø§ÙØ£Ø¨ÙØ§Ø¡ Ø¶Ø¹ÙÙØ© ÙØ±ÙØ¶Ø©. ÙÙØ°Ù Ø§ÙØ´Ø®ØµÙØ© ØºÙØ± Ø§ÙØ³ÙÙÙØ© Ø³ØªØµØ¨Ø ÙØ´ÙÙØ© ÙÙÙ ÙÙ ØµØºØ±ÙÙ ÙØÙÙ Ø£ØµØ¨ØÙØ§ Ø´Ø¨Ø§ÙØ§ ÙØ±Ø¬Ø§ÙØ§.